KOMUNIKASI INTERPERSONAL GURU DALAM MENUNJANG MINAT BELAJAR SISWA SISWI MADRASAH ALIYAH SEPAKU DI KAWASAN IBU KOTA NEGARA NUSANTARA - Royanti, Royanti; Wahdiansyah, Wahdiansyah; Rahmawati, Sulis (Journal of Sustainable Transformation, 2023)
Interpersonal communication is used in the form of achieving goals, for example, communication between teachers and students, and students and students. The purpose of education would not be realized without skilled and creative educators in carrying out the educational process as communication skills in finding out the strategies for supporting and inhibiting factors that support students' learning interests. Based on that reason, this study took the issue of teacher interpersonal communication in supporting students' learning interests at Madrasah Aliyah Sepaku using a descriptive qualitative method. Data collection tools include interview observations and documentation. The results of this study indicated that the interpersonal communication skills of teachers towards their students during the learning process in class such as creating a conducive and pleasant classroom atmosphere could support students' learning interest and intimacy and concern for their students. Factors supporting interest in learning at school were shown by the types of subjects and more focus during the learning process. The inhibiting factors of students' interest in learning were shown by teachers’ quality in teaching and the difficulty accepting subjects. If students are interested in learning activities, the process of learning would be better.